Cost-effective retrofit of a palm oil refinery using pinch analysis - Wan Alwi, Sharifah Rafidah; Tamar Jaya, Muhammad Azan; Abdul Manan, Zainuddin (Penerbit UTM Press, 2009)
A palm oil refinery involves energy-intensive processes. Maximizing thermal efficiency of palm oil refinery is crucial for the plant profitability. This work implements a pinch analysis retrofit technique to maximize heat recovery and thermal efficiency of a palm oil refinery, subject to the existing process constraints. The procedures involve setting the maximum heat recovery targets and cost-effective retrofit of the heat exchanger network (HEN). Application of the technique on a palm oil refinery results in reduction of 700 kW (21%) heating and cooling loads or a saving of RM370,787, incurring a capital investment of about RM656,293 and a payback period of 1.77 years.